Mental health expert’s perspective on risk and protective factors of suicide ideation in Patients with OCD and depression - Roma Sarwar; Alia Asmat (BMC Psychiatry)
Abstract Background Suicidal ideation and behavior present profound challenges in mental health care, particularly among individuals contending with Depression and Obsessive-Compulsive Disorder (OCD). While existing research has elucidated the intricate pathways through which depression and OCD independently contribute to suicide risk, there remains a critical gap in understanding the interplay between these disorders in shaping suicidal tendencies. Aim This qualitative study aims to address this gap by exploring expert’s perspective about the risk and protective factors associated with suicidal ideation among individuals diagnosed with depression and OCD. Method Through semi-structured interviews with mental health experts, thematic analysis was employed to uncover the cognitive, emotional, and environmental stressors influencing suicidal thoughts and behaviors in this clinical population. Results Findings reveal multifaceted cognitive vulnerabilities, adverse childhood experiences, and familial factors as prominent risk factors, while coping skills, social support, and religious beliefs emerged as key protective factors. Conclusion By illuminating the complex interplay of factors contributing to suicidal ideation in the context of comorbid depression and OCD, this study provides valuable insights for the development of targeted interventions aimed at mitigating suicide risk and improving outcomes for affected individuals.